Analisis Kejadian Stunting Pada Balita Ditinjau Dari Pengetahuan Ibu Di Wilayah Kerja Puskesmas Tanjung Leidong - Arlina Sinaga; Lasria Simamora; Deby Cyntia Yun (Pusat Riset dan Inovasi Nasional, 2024)
Riskesdas data for 2018 shows that the prevalence of stunted toddlers in Indonesia is 30.8%. Conditions in Indonesia based on data from the 2019 Study on the Nutritional Status of Toddlers in Indonesia are still relatively high, where the prevalence of stunting is 27.67%. This figure shows that stunting in Indonesia is still higher than the prevalence in Southeast Asia of 24.7%. Based on data from the health profile of North Sumatra province in 2019, it is known that short toddlers in North Sumatra Province are 2.61%, where for the districts/cities the highest stunting under fives are Gunung Sitoli (41.51%), West Nias (16.61%) and Samosir (11.97%). For North Labuhan Batu Regency it is at 0.72%. This research is an observational analytical study using a retrospective case control study design which aims to determine the relationship between maternal knowledge and the incidence of stunting among toddlers in the Tanjung Leidong Community Health Center work area, conducted from April – June 2022. The sample size was 36 people, using a sampling technique. in this research is Consecutive sampling. The results showed that maternal knowledge was related to stunting with a p value of 0.007<0.05 with an odds ratio of 9.1 (1.99 – 41.44). It is hoped that an integrated and multisectoral program is needed to increase maternal nutritional knowledge in increasing knowledge related to stunting prevention.